2007
DOI: 10.1002/ppul.20744
|View full text |Cite
|
Sign up to set email alerts
|

Congenital central hypoventilation syndrome: PHOX2B genotype determines risk for sudden death

Abstract: Summary. Objective: Children with Congenital Central Hypoventilation Syndrome (CCHS) have cardiovascular symptoms consistent with the autonomic nervous system dysregulation/ dysfunction (ANSD) phenotype. We hypothesized that children with CCHS would have a relationship between PHOX2B genotype and two clinically applicable cardiovascular measures of ANSD: duration of longest r-r interval and longest corrected QT interval (QTc). Materials and Methods: We studied 501 days of Holter recordings from 39 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 31 publications
1
69
0
1
Order By: Relevance
“…They also showed that phenotype severity increased with increasing polyalanine expansion size. Increased repeat length was associated with severe respiratory symptoms, a long R-R interval in Holter monitoring, and facial phenotypes [34,35]. Results by Trochet et al [8] strongly supported this genotypephenotype interaction.…”
Section: Molecular Geneticssupporting
confidence: 66%
See 1 more Smart Citation
“…They also showed that phenotype severity increased with increasing polyalanine expansion size. Increased repeat length was associated with severe respiratory symptoms, a long R-R interval in Holter monitoring, and facial phenotypes [34,35]. Results by Trochet et al [8] strongly supported this genotypephenotype interaction.…”
Section: Molecular Geneticssupporting
confidence: 66%
“…Review of these results demonstrated that HSCR and neural crest tumors were more frequently associated with missense or frameshift mutations of PHOX2B than with the polyalanine expansion. This led to the conclusion that missense or frameshift mutations produce more severe dysfunction in PHOX2B [8,[32][33][34][35]. How ever, the relationship was not strict, and further study of additional cases is needed to confirm the hypothesis.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…This includes the potential for pupillometry to predict risk for other pathology (i.e., risk for cardiac sinus pauses) as a sign of cardiac ANSD (10). Accordingly, future steps would include systematic investigation of which, if any, phenotypic features in CCHS are associated with the various pupillary measurements.…”
Section: Pupillometry In Cchsmentioning
confidence: 99%
“…Missense, nonsense, frameshift, and stop codon mutations in the PHOX2B gene, referred to as nonpolyalanine repeat expansion mutations (NPARMs), account for the remaining mutations in CCHS. Quantitative assessment of the respiratory control and ANSD features of CCHS by PHOX2B genotype has identified a graded genotype-phenotype relationship between mutation repeat length and ventilatory requirements (3,4), Hirschsprung disease (8,9), neural crest tumors (8,9), and cardiac sinus pauses (10).…”
Section: Ongenital Central Hypoventilation Syndrome (Cchs) Ismentioning
confidence: 99%
“…Chest X-ray and potential chest CT, comprehensive neurological evaluation, potential muscle biopsy, and echocardiogram should exclude as a primary lung disease, ventilatory muscle weakness and cardiac disease. Seventytwo hours of Holter monitoring may determine aberrant cardiac rhythm abnormalities including decreased beat-tobeat heart rate variability [72]. Causative gross anatomic brain/brainstem lesions should be ruled out following a CT or/and MRI scan [73].…”
Section: Diagnosis and Managementmentioning
confidence: 99%